Eksplorasi Penerapan Kurikulum Berbasis Teknologi bagi Siswa MI Nurul Huda Kabupaten Kediri - Wahyuningtias, Tri; Azzahra, Noer Adila; Sodik, Mochammad Jafar; Muizzah, Ulfiatul (Asian Journal of Early Childhood and Elementary Education, 2023)
The lack of dissemination of information regarding technology-based learning is a problem in developing new curricula. This is in line with the problems that exist at MI Nurul Huda, Kediri Regency, such as; 1) The madrasah only applies technology in a few conditions because there is no clear information regarding the implementation of technology-based learning by the Ministry of Religion; 2) The implementation of technology in the Computer-Based National Assessment (ANBK) is only applied to class V students; 3) The use of e-books in learning is still teacher-centered or teacher-focused; 4) Implementation of the Merdeka curriculum only in grades I-IV; 5) Lack of facilities and infrastructure to support technology-based curriculum development; and 6) The location of the madrasah is located in a rural area which causes limited access. The aim of this research is to find out whether there is an application of technology-based learning at 3T schools, namely MI Nurul Huda, Kediri Regency. The data collection technique used interview observation with one of the MI teachers, Nurul Huda.